Primary chronic pain as a somatization of distress - Burdeinyi Андрій; Stashenko Станіслав (Psychosomatic Medicine and General Practice, 2023)
Relevance. The direct functional significance of pain is to signal the action of a stimulus, damage to the integrity of the organism or its individual structures. A number of scientists have approached the study of pain as a physiological defense mechanism, during which we understand the principles of its emergence, course, localization, and ways to overcome pain sensations through pharmacological, physical, and instrumental methods. However, the problem of pain arises when the physiological substrate is absent or does not correspond to the strength or duration of the manifestation. This is where we can talk about pain of a psychogenic nature, which despite a number of studies that are currently underway, still remains difficult to treat. Objective. To improve the effectiveness of medical-psychological assistance by studying the nature and patterns of pain syndrome in patients with primary chronic pain with subsequent psycho-correction and the use of psychotherapeutic interventions. Methods. The study design was a monocentric randomized controlled trial with parallel groups. The study involved 14 individuals with primary chronic pain syndrome, which corresponded to ethical and deontological norms according to the principles set out in the Helsinki Declaration. The tools used in the study included the SPAASMS subjective pain assessment scale, the somatic symptoms questionnaire (SSS-8), the Bass-Darky aggressiveness and hostility level questionnaire (BDHI), as well as the Chaban O.S. quality of life assessment scale (CQLS). Results. At the completion of the study, a statistically significant difference was observed for all clinical parameters between the experimental and control groups. Comparison of the values of the scale in the experimental group on days 1 and 42 demonstrated statistically significant changes in all four indicators. However, this study reveals a limited sample, which in turn allows for expanding the sample size and investigating the phenomenon of applied interventions in future pilot studies, as the primary results provide a qualitative and positive trend in reducing the effects and impact of primary chronic pain, as well as improving the quality of life indicator. Conclusions. The results of this study confirm the effectiveness of psychological interventions, as well as psychological interventions for reducing the subjective sensation of pain syndrome, symptoms of somatization, aggressive and hostile reactions, and improving the quality of life in individuals suffering from primary chronic pain.